2010
DOI: 10.1007/s11999-009-1219-6
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps and Hamstrings Muscle Dysfunction after Total Knee Arthroplasty

Abstract: Background/rationale Although TKA reliably reduces pain from knee osteoarthritis, full recovery of muscle strength and physical function to normal levels is rare. We presumed that a better understanding of acute changes in hamstrings and quadriceps muscle performance would allow us to enhance early rehabilitation after TKA and improve long-term function. Questions/purposes The purposes of this study were to (1) evaluate postoperative quadriceps and hamstrings muscle strength loss after TKA and subsequent recov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
133
2
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(153 citation statements)
references
References 35 publications
(53 reference statements)
16
133
2
2
Order By: Relevance
“…Strength testing of the hip abductors was performed while participants were sidelying positioned in 0°of abduction/adduction and flexion/extension with a strap to stabilize the pelvis [26,36]. Maximal strength testing of the knee extensors and flexors was performed while patients were seated and stabilized with a shoulder harness and waist strap in 85°of hip flexion and 60°of knee flexion as previously described [31,47]. Data were sampled using a BiopacData Acquisition System at a sampling frequency of 2000 Hz (MP 150; Biodex Medical Systems, Inc, Shirley, NY, USA) and analyzed using AcqKnowledge software, Version 3.8.2 (Biodex Medical Systems, Inc).…”
Section: Strength Testing Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Strength testing of the hip abductors was performed while participants were sidelying positioned in 0°of abduction/adduction and flexion/extension with a strap to stabilize the pelvis [26,36]. Maximal strength testing of the knee extensors and flexors was performed while patients were seated and stabilized with a shoulder harness and waist strap in 85°of hip flexion and 60°of knee flexion as previously described [31,47]. Data were sampled using a BiopacData Acquisition System at a sampling frequency of 2000 Hz (MP 150; Biodex Medical Systems, Inc, Shirley, NY, USA) and analyzed using AcqKnowledge software, Version 3.8.2 (Biodex Medical Systems, Inc).…”
Section: Strength Testing Proceduresmentioning
confidence: 99%
“…All patients were given visual targets from the dynamometer's output and strong verbal encouragement during each trial. Maximal voluntary isometric contractions for all muscle groups were performed twice; however, if maximal torque during the first two trials differed by more than 5%, a third trial was performed, as previously described [18,[46][47][48]. The trial with the highest torque was normalized to body mass (kg) and used for analysis [1].…”
Section: Strength Testing Proceduresmentioning
confidence: 99%
“…In their clinical study, Stevens-Lapsley et al [31] reported that quadriceps strength decreased by 52 % and hamstring strength by 48 % at one month after TKA. In the present sample, at two months after surgery, knee extension strength showed a decrease from preoperative values of 49 % in the exercise group and 55 % in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it will be necessary to study the effects of MQS on muscle strength and walking ability for the elderly with TKA for more than 4 weeks. Furthermore, a recent study 20) suggested that rehabilitation programs after TKA should focus on improving the strength of the quadriceps femoris and h a m s t r i n g m u s c l e s . I n t h i s r e g a r d , M Q S m a y simultaneously enhance the gluteus maximus muscles along with the quadriceps femoris and hamstring muscles; therefore, it may be appropriate for elderly persons' early rehabilitation after TKA.…”
Section: Discussionmentioning
confidence: 99%